Francisella RNA polymerase contains a heterodimer of non-identical α subunits - Mukhamedyarov, Damir (BioMed Central, 2011)
BACKGROUND: All sequenced genomes of representatives of the Francisella genus contain two rpoA genes, which encode non-identical RNA polymerase (RNAP) subunits, α1 and α2. In all other bacteria studied to date, a dimer of identical α subunits initiates the assembly of the catalytically proficient RNAP core (subunit composition α(2)ββ'). Based on an observation that both α1 and α2 are incorporated into Francisella RNAP, Charity et al. (2007) previously suggested that up to four different species of RNAP core enzyme might form in the same Francisella cell. RESULTS: By in vitro assembly from fully denatured state, we determined that both Francisella α subunits are required for efficient dimerization; no homodimer formation was detected. Bacterial two-hybrid system analysis likewise indicated strong interactions between the α1 and α2 N-terminal domains (NTDs, responsible for dimerization). NTDs of α2 did not interact detectably, while weak interaction between α1 NTDs was observed. This weak homotypic interaction may explain low-level transcription activity observed in in vitro RNAP reconstitution reactions containing Francisella large subunits (β', β) and α1. No activity was observed with RNAP reconstitution reactions containing α2, while robust transcription activity was detected in reactions containing α1 and α2. Phylogenetic analysis based on RpoA resulted in a tree compatible with standard bacterial taxonomy with both Francisella RpoA branches positioned within γ-proteobacteria. The observed phylogeny and analysis of constrained trees are compatible with Francisella lineage-specific rpoA duplication followed by acceleration of evolutionary rate and subfunctionalization. CONCLUSIONS: The results strongly suggest that most Francisella RNAP contains α heterodimer with a minor subfraction possibly containing α1 homodimer. Comparative sequence analysis suggests that this heterodimer is oriented, in a sense that only one monomer, α1, interacts with the β subunit during the α(2)β RNAP subassembly formation. Most likely the two rpoA copies in Francisella have emerged through a lineage-specific duplication followed by subfunctionalization of interacting paralogs.